Child development a practical introduction - Crowley, Kevin (Los Angeles Sage, 2017)
"Focusing on the earliest years (0-8), the new Second Edition of this best-selling textbook continues to provide a comprehensive overview of the research, theory, and current practice in the field of child development"--Provided by publisher.
Chapter 1: Introduction to Child Development -- Chapter 2: Policy and Early Years Practice -- Chapter 3: Researching Child Development -- Chapter 4: Physical and Brain Development -- Chapter 5: Cognition and Memory -- Chapter 6: Disorders and Development -- Chapter 7: Health and Development -- Chapter 8: Emotional Development -- Chapter 9 Social Development -- Chapter 10: Language and Literacy -- Chapter 11: The Role of Play -- Chapter 12: The Role of the Adult
Keywords: Child development; Child care